Depth Imaging Enhancement Using Reverse Time Migration - Alashloo, S.Y.M. (Institute of Physics Publishing, 2017)
Imaging the subsurface with complex structures and steeply dipping salt boundaries is a challenging task in seismic exploration. Between two main categories of seismic migration, wavefield-continuation methods have been more successful than ray-based ones. Wavefield-continuation migration constructs source and reflection wavefields as a function of depth or time by directly solving one-way or two-way wave equations. Consequently, this technique has two benefits. First, compared to Kirchhoff migration, it does not use high-frequency approximation and can more accurately propagate wavefields in shallow depths. Secondly, it can naturally handle multi-paths or multi-arrivals. Reverse time migration (RTM) is a wavefield-continuation method which is accepted as the best migration method currently available for imaging complicated geology. The main objective of this research is to improve imaging of complex structures by utilizing the RTM technique. Two models, involving anticlines, faults, etc., are employed to test the technique. The imaging results demonstrated that the RTM method succeeded to image the flanks, remove noises and improve the resolution. © Published under licence by IOP Publishing Ltd.